Issues in entrepreneurship contracts, corporate characteristics, and country differences, 2002 - Libecap, Gary D. (JAI, 2003)
Entrepreneurship is recognized as critical for the growth of both individual firms and overall economies. Entrepreneurship fosters the introduction of new products, processes and organizations. It provides the flexibility and dynamism required for responding to new market opportunities and challenges. Despite all of this, entrepreneurship is not well understood. Who is an entrepreneur? What conditions promote entrepreneurship? How does it differ across firms and across countries? Fortunately, as revealed in the chapters included in this volume, there is an active research agenda on entrepreneurship. There is information for academics, business people, and a lay audience on vital issues including, collaborations between R&D firms, corporate entrepreneurship and firm growth, technological change and entrepreneurship in Taiwan, venture capital, cross country comparisons of entrepreneurship by women, the characteristics of high-tech enterepreneurs, and the leading US business plans competition, MOOT Corp.
Keywords: Entrepreneurship -- Cross-cultural studies.; Business -- Cross-cultural studies.; Industrial management -- Cross-cultural studies.; Contracts -- Cross-cultural studies.; Comparative law.; Comparative management.; Comparative economics.; elektronické knihy; electronic books